2002
DOI: 10.5194/aab-45-213-2002
|View full text |Cite
|
Sign up to set email alerts
|

Systematic effects on activity, milk yield, milk flow rate and electrical conductivity

Abstract: SummaryThe traits activity, milk yield, milk flow rate and electrical conductivity were analysed in preparation for automatic oestrus detection. Collection of data was performed on a commercial dairy farm and milking took place in a rotary milking parlour. Between February and December 1998 1,090,031 observations from 2,422 Holstein Friesian cows were accumulated. Around 30% of cows were milked thrice daily. For each trait and each cow a daily value was calculated. The fixed effects test day, parity, calving s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
3
6
1
Order By: Relevance
“…Correction for daily milk yield indicates differences in milking duration to be a consequence of the observed differences in milk flow. Increased AMF with parity corroborates previous reports (Firk et al, 2002), while Petersen et al (1986) also reported increasing PMF with increasing parity number. Higher PMF in older animals may be associated with the possible weakening of the teat end with age or as a result of damage of the teat sphincter as parity number increases due to harmful effects of machine milking (Maltz et al, 2000).…”
Section: Effect Of Parity On Udder Health and Milking Characteristicssupporting
confidence: 89%
“…Correction for daily milk yield indicates differences in milking duration to be a consequence of the observed differences in milk flow. Increased AMF with parity corroborates previous reports (Firk et al, 2002), while Petersen et al (1986) also reported increasing PMF with increasing parity number. Higher PMF in older animals may be associated with the possible weakening of the teat end with age or as a result of damage of the teat sphincter as parity number increases due to harmful effects of machine milking (Maltz et al, 2000).…”
Section: Effect Of Parity On Udder Health and Milking Characteristicssupporting
confidence: 89%
“…measuring of milk temperature shows a high interest of "false positive" animals and the results are not usable. These problems with other physiological animal parameter are also confirmed by other authors (Gartland et al 1976;Firk et al 2002). The measuring of progesterone is very expensive and problematic in its precision (moore & Spahr 1991;Eddy & Clark 1987;Nebel et al 1987).…”
supporting
confidence: 66%
“…The higher activity in primiparous cows might be directly related to the higher number of visits to the feeding trough observed in the current study. The statement of Ulbrich et al (2004) and the findings of Firk et al (2002) might explain the observed result of a higher feed intake amount in older cows, accompanied by fewer visits to the feeding trough and less time spent feeding per day.…”
Section: Discussionmentioning
confidence: 76%
“…However, according to Ulbrich et al (2004), older cows have a higher velocity of feed intake when compared to heifers. Furthermore, in the study of Firk et al (2002) it was found that activity, measured by pedometers, decreased significantly with increasing number of parity. The higher activity in primiparous cows might be directly related to the higher number of visits to the feeding trough observed in the current study.…”
Section: Discussionmentioning
confidence: 99%